PERSEPSI MAHASISWA TERHADAP PENGGUNAAN METODE RESITASI VIDEO PADA MATA KULIAH KEWARGANEGARAAN PROGRAM STUDI TADRIS IPS UIN DATOKARAMA PALU - Zaifullah zaifullah (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) IAIN Palu, 2022)
The aim of the study was to find out how students perceive the use of the video recitation method in increasing students' understanding of civics courses. The research method used by the author is descriptive quantitative with a survey approach which aims to provide a general description of the object under study. This research was conducted on students of the 1st semester Social Sciences tadris study program, Faculty of Tarbiyah and Teaching Sciences, UIN Datokarama Palu. The population of this study was 30 people, based on the consideration of the population, this study was classified as a sample researcher. Data collection techniques through interviews, questionnaires and documentation. This study uses qualitative descriptive analysis techniques, and the results of this study will be presented using tools such as frequency tables and percentage tables. The results showed that the provision of the video recitation method was effective in increasing understanding of the material in Citizenship courses that were previously delivered by lecturers, but in its implementation it must be supported by the provision of networks or maximum internet service providers in classrooms to be a determining factor for the successful implementation of the method.